2015
DOI: 10.4209/aaqr.2014.08.0158
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Particulate Matter during Haze and Fog (Pollution) Episodes over Northeast China, Autumn 2013

Abstract: Mass concentrations of particulate matter (PM), including PM 1.0 , PM 2.5 and PM 10 , were measured from October 13 th to November 30 th 2013 at eight sites in Northeast China to evaluate their variations during pollution periods. Five major pollution periods were identified during the autumn of 2013. The maximum daily average PM 2.5 concentrations were 437 ± 85 µg/m 3 and 322 ± 50 µg/m 3 in Harbin and Shenyang, respectively. The minimum was 75 ± 28 µg/m 3 in Dandong. The presence of finer particles was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 41 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Previous studies indicated that the increase in PM 2.5 mass concentration contributed to visibility impairment significantly in China (Cao et al, 2012;Han et al, 2013;Li et al, 2015;Han et al, 2016). The relationships between visibility and PM 2.5 mass concentrations for both long-lasting haze and fog-haze mixed events are shown in Fig.…”
Section: Relationship Between Visibility and Pm 25 Mass Concentrationmentioning
confidence: 97%
“…Previous studies indicated that the increase in PM 2.5 mass concentration contributed to visibility impairment significantly in China (Cao et al, 2012;Han et al, 2013;Li et al, 2015;Han et al, 2016). The relationships between visibility and PM 2.5 mass concentrations for both long-lasting haze and fog-haze mixed events are shown in Fig.…”
Section: Relationship Between Visibility and Pm 25 Mass Concentrationmentioning
confidence: 97%
“…Beijing, the capital of China, a megacity with approximately 22 million inhabitants (Beijing Statistical Yearbook, 2015), has frequently suffered from extreme haze, which is characterized by high fine particle (i.e., PM 2.5 ) loading (Sun et al, 2006;Li et al, 2015). These fine particles have adverse effects on human health, can scatter and absorb the incident light and lead to atmospheric opacity, and horizontal visibility degradation (Han et al, 2015;Jing et al, 2015;Tao et al, 2015;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In China, air pollution in megacities is mainly caused by the drastic economic growth, together with the rapid industrialization and the wide urbanization (e.g., Wang et al, 2014a, b;Li et al, 2015;Lang et al, 2017). China has been suffering from serious air quality problems, mostly related to fine particulate matter (Jiang et al, 2015;Lv et al, 2015;San Martini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%